2005
DOI: 10.1161/circulationaha.104.532820
|View full text |Cite
|
Sign up to set email alerts
|

Distal Protection Improved Reperfusion and Reduced Left Ventricular Dysfunction in Patients With Acute Myocardial Infarction Who Had Angioscopically Defined Ruptured Plaque

Abstract: Background-Distal protection, in the Saphenous Vein Graft Angioplasty Free of Emboli (SAFER) trial, is demonstratedto prevent distal embolism in the percutaneous coronary intervention of saphenous vein graft. However, in the Enhanced Myocardial Efficacy and Recovery by Aspiration of Liberated Debris (EMERALD) trial, it was not effective in the percutaneous coronary intervention of native coronary arteries in patients with acute myocardial infarction (AMI). We hypothesized that its effectiveness would be determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 44 publications
1
59
0
1
Order By: Relevance
“…Ruptured plaque has been reported to be related to distal embolization by stenting 19) ; therefore, this finding corresponded with our results. However, plaque complexity was not significantly higher in multivariate analysis than intense yellow plaque because the intense yellow plaque did not necessarily correspond with either plaque complexity or thrombus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ruptured plaque has been reported to be related to distal embolization by stenting 19) ; therefore, this finding corresponded with our results. However, plaque complexity was not significantly higher in multivariate analysis than intense yellow plaque because the intense yellow plaque did not necessarily correspond with either plaque complexity or thrombus.…”
Section: Discussionsupporting
confidence: 93%
“…Although ruptured yellow plaques and intracoronary massive thrombi in the culprit plaques of acute coronary syndrome were frequently observed in a previous study 21) , there were no massive thrombi in this study because all patients had stable angina pectoris and only mural thrombi. A previous study suggested plaque debris to more strongly influence both the slow-flow phenomenon and distal embolization after stenting than thrombi 19) . As a result, mural thrombi are not considered to likely be either a powerful predictor or to have the ability to induce post-procedural myocardial injury in cases of In this study, the frequency of pre-dilatation, maximum pressure inflation and the total inflation time were not found to influence post-procedural myocardial injury, while the total stent length was associated with post-procedural myocardial injury.…”
Section: Discussionmentioning
confidence: 94%
“…Directional and rotational atherectomy has a higher risk of no-reflow than balloon angioplasty. 26 Thrombolytic drugs can activate the complement and kinin systems, and increase the concentration of IL-6 and thrombin. Endothelium damage results in collagen exposure.…”
Section: (V) the Plaque Chip And Micro-thrombusmentioning
confidence: 99%
“…Using glycoprotein IIb/IIIa receptor blockade might have reduced the chances of additional improvement through distal protection in the EMERALD trial. Mizote et al(2005) revealed that distal protection reduced microcirculation damage and left ventricular dysfunction in patients with AMI who had ruptured plaque. Yoon et al(2006) also found that distal protection may effectively preserve the microvascular integrity of the myocardium during primary PCI in AMI patients.…”
Section: Discussionmentioning
confidence: 99%